Frontiers in the Growth of Complex Oxide Thin Films: Past, Present, and Future of Hybrid MBE. (21st December 2017) - Brahlek, Matthew; Gupta, Arnab Sen; Lapano, Jason; Roth, Joseph; Zhang, Hai‐Tian; Zhang, Lei; Haislmaier, Ryan; Engel‐Herbert, Roman
Abstract: Driven by an ever‐expanding interest in new material systems with new functionality, the growth of atomic‐scale electronic materials by molecular beam epitaxy (MBE) has evolved continuously since the 1950s. Here, a new MBE technique called hybrid ‐MBE ( h MBE) is reviewed that has been proven a powerful approach for tackling the challenge of growing high‐quality, multicomponent complex oxides, specifically the AB O3 perovskites. The goal of this work is to (1) discuss the development of h MBE in a historical context, (2) review the advantageous surface kinetics and chemistry that enable the self‐regulated growth of AB O3 perovskites, (3) layout the key components and technical challenges associated with h MBE, (4) review the status of the field and the materials that have been successfully grown by h MBE which demonstrate its general applicability, and (5) discuss the future of h MBE in regards to technical innovations and expansion into new material classes, which are aimed at expanding into industrial realm and at tackling new scientific endeavors. Abstract : The development of hybrid molecular beam epitaxy is described from a historic, scientific, and technical perspective. The rapid progress in this expanding field is comprehensively summarized and emphasis is placed on the growth aspects of ternary and quaternary perovskite oxides with different chemistries, the control over cation stoichiometry and its direct ramification in thin film quality.